The Effect of Interpersonal Communication, Organizational Culture and Work Environment on the Performance of Education and Culture Office Employees of Pidie Jaya Regency - Suryadi, Suryadi; Abubakar, Fauzi (Singkite Journal, 2022)
This study aims to analyze descriptively and verification based on the results of a survey of employee data at the Education and Culture Office of Pidie Jaya Regency, Aceh Province. Related to the direct and indirect influence of interpersonal communication aspects, organizational culture and work environment factors on employee performance. The results of the path analysis show, 1) There is a significant influence between communication factors between employees on employee performance, amounting to 37.06%. 2) There is a positive and significant influence of organizational culture on employee performance, which is 30.12%. 3) There is a positive and significant effect of work environment variables on employee performance of 39.01%. And 4) simultaneously communication between employees, organizational culture and work environment contribute to the increase in the performance of the employees of the Education and Culture Office of Pidie Jaya Regency by 60.3%. While the remaining (remaining) of the role variables that were not examined were 39.7%, such as aspects of discipline, work motivation, and leadership style